2019
DOI: 10.1021/acs.iecr.8b05451
|View full text |Cite
|
Sign up to set email alerts
|

Co-Based Catalysts Supported on Silica and Carbon Materials: Effect of Support Property on Cobalt Species and Fischer–Tropsch Synthesis Performance

Abstract: The influence of different support surfaces and physical structures on cobalt species and catalytic Fischer–Tropsch synthesis (FTS) performance has been investigated by using silica or mesoporous carbon as support. All the three catalysts Co/SBA-15, Co/SiO2, and Co/CMK-3 behaved differently in the FTS test and showed characteristic cobalt species. After calcination in argon, Co3O4 was prominent on both Co/SBA-15 and Co/SiO2 because of the stronger metal–support interaction. However, the weaker metal–support in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 51 publications
6
17
0
Order By: Relevance
“…The Co 2p 3/2 peaks are at 779.7-781.3 eV, and the peaks at 794.7-796.5 eV are attributed to Co 2p 1/2 spin-orbital peaks. [42] These binding energies are close to those found for Co/C catalysts and attributed to Co 3 O 4 , whose Co 2p spin orbital splitting value is 15.0 � 0.1 eV. [42] The energy separation between Co 2p 1/2 and Co 2p 3/2 was around 15 eV for all samples.…”
Section: Cobalt Particle Size Crystallographic Phase and Compositionsupporting
confidence: 71%
See 1 more Smart Citation
“…The Co 2p 3/2 peaks are at 779.7-781.3 eV, and the peaks at 794.7-796.5 eV are attributed to Co 2p 1/2 spin-orbital peaks. [42] These binding energies are close to those found for Co/C catalysts and attributed to Co 3 O 4 , whose Co 2p spin orbital splitting value is 15.0 � 0.1 eV. [42] The energy separation between Co 2p 1/2 and Co 2p 3/2 was around 15 eV for all samples.…”
Section: Cobalt Particle Size Crystallographic Phase and Compositionsupporting
confidence: 71%
“…[42] These binding energies are close to those found for Co/C catalysts and attributed to Co 3 O 4 , whose Co 2p spin orbital splitting value is 15.0 � 0.1 eV. [42] The energy separation between Co 2p 1/2 and Co 2p 3/2 was around 15 eV for all samples. Based on these results, it appears that there is no significant difference from one catalyst to another in terms of charge transfer.…”
Section: Cobalt Particle Size Crystallographic Phase and Compositionsupporting
confidence: 71%
“…In contrast, for the catalysts reduced at 450 and 500 °C, CO conversion decreased to 42.5% and 33.3%, respectively, which could be due to the increase of Co particle size [80]. During auto-reduction, the transformation from metal oxide to the metallic phase can determine two crucial parameters: the particle size and the MSI [108,215]. It was reported that the incorporation of nitrogen atoms significantly changes the chemical environment of carbon supports, which results in interfacial electronic interactions [108].…”
Section: Effect Of Activation Conditionsmentioning
confidence: 95%
“…Carbon supports having different nanostructures that are commonly used include, CNF [144,[209][210][211][212], CNT [127,213], AC [97], carbon sphere (CS) [91,211], mesoporous carbon (CMK) [107,[214][215][216], or graphene nanosheets (GNS) [155,217,218]. The nature of the carbon support has impacts on MSI, mass and heat transfer, stability, and mechanical and thermal resistance [219].…”
Section: Effect Of the Type Of Carbon Supportmentioning
confidence: 99%
“…Many efforts have been focused on the structure–function relationship of heterogeneous catalysts for syngas conversion. Over the past decades, carbon material catalysts have been widely used in heterogeneous catalysis because of their inert surface and unique electron transfer properties, displaying special catalytic property and prospect compared with oxide supports. The inert surface of carbon usually led to a weak interaction between the metal and carbon material, which avoided forming irreducible metal spinel and made the active metal to be used efficiently. , In addition, a carbon material with a higher degree of graphitization promoted the auto-reduction because of an easier electron transfer between metal oxides and the carbon material. However, the weak metal–support interaction may cause heavy sintering or agglomeration of the active metal, resulting in rapid deactivation during syngas conversion such as Fischer–Tropsch synthesis (FTS). , Modulating the surface of the carbon material to anchor the active metal or confining active metal in the carbon material have been proved to avoid sintering or agglomeration efficiently. , Confining cobalt particles in the carbon nanotubes (CNTs) or the narrow region of the core–shell structure of Co@C derived from MOFs improved catalytic stability in FTS. , Meanwhile, an extended contacting time of reaction intermediates in the carbon nanotubes promoted the chain growth to form long chain hydrocarbons and less CH 4 in FTS. ,, The Co@C catalysts derived from carbonization of MOFs had different carbon chain growth probabilities that resulted in different selectivities to CH 4 and C 5+ hydrocarbons because of different cobalt particle sizes and varied carbon shell properties. , The CH 4 selectivity showed a negative correlation with the Co 0 size until particles increased to about 7–8 nm. It was verified that the smaller cobalt particles could generate more high-energy active sites, which produced more methane. , Results about CH 4 selectivity on Co-based catalysts related with carbon materials are listed in Table S1. ,,, Although the cobalt particle size in carbon support was big enough to prevent more methane formation, CH 4 selectivity was exceptionally high compared with oxide-supported catalysts.…”
Section: Introductionmentioning
confidence: 99%